Optimisation of the composition of safe dental gel with IL-1β antagonist for the treatment of inflammatory periodontal diseases - Dmytriieva, О. О.; Bielenichev, I. F.; Burlaka, B. S.; Дмитрієва, О. О.; Бєленічев, Ігор Федорович; Бурлака, Богдан Сергійович (Запорізький державний медико-фармацевтичний університет, 2024)
Aim. The study aims to develop the composition of the oromucosal gel with the IL-1β interleukin antagonist for complex treatment of inflammatory periodontal diseases. Materials and methods. Experimental studies were conducted based on the Department of Medicines Technology of Zaporizhzhia State Medical and Pharmaceutical University and the Training Medical and Laboratory Center of Zaporizhzhia State Medical and Pharmaceutical University of the Ministry of Health of Ukraine. As an active component, in the recipe of oromucosal gel, used antagonist of the interleukin IL-1B. Excipients: D-panthenol (the plasticizer), carboxymethylcellulose sodium salt (the viscosity modifier and mucoadhesive component), Tween-80 (the enhancer absorption), benzalkonium chloride (the preservative), sodium hydrophosphate + citric acid (the phosphate buffer solution), purified water. The experiments used existing and auxiliary ingredients of pharmaceutical purity, which were obtained from Sinbias LLC, Istok-Plus LLC, LLC “Mobile Medical”. For the design of the experiment, the methodology of the response surface (Box-Behnken Design) is used: Na CMC, Tween-80, D-panthenol; and four answers: pH, viscosity test, system type, mucoadhesive properties. Research methods: rheological research (viscosity test, amplitude test, frequency test, mucoadhesive test, thixotropy test) performed in oscillation mode on the modular compact Rheometer Anton Paar MCR 302 (CP50-1 SN71317), which, compared to cylindrical devices, requires a much smaller amount of gel sample and allows the planned tests in the oscillation mode, the temperature in the experiments was provided with a built-in thermostat (Peltier Temperature Control, C-PTD 200). Мета роботи – розроблення складу оромукозного гелю з антагоністом інтерлейкіну IL-1β для комплексного лікування запальних захворювань пародонта. Матеріали і методи. Експериментальні дослідження здійснили на базі кафедри технології ліків Запорізького державного медико-фармацевтичного університету та Навчально-наукового медико-лабораторного центру Запорізького державного медико-фармацевтичного університету МОЗ України. Як компонент з активною дією в рецептурі оромукозного гелю використали антагоніст інтерлейкіну IL-1b. Допоміжні речовини: D-пантенол (пластифікатор), карбоксиметилцелюлози натрієва сіль (модифікатор в’язкості, мукоадгезивний компонент), твін-80 (енхасер адсорбції), бензалконію хлорид (консервант), динатрію гідрофосфат + кислота лимонна (фосфатний буферний розчин), вода очищена. В експериментах використані активні й допоміжні інгредієнти фармацевтичної чистоти, які отримано від ТОВ НВФ «СІНБІАС», ТОВ «Исток-Плюс», ТОВ «МОБІЛЬ МЕДІКАЛ». Для дизайну експерименту використано методологію поверхні відповіді (Box-Behnken Design) з трьома рівнями факторів (Na CMC, Tween-80, D-panthenol) та чотирма відповідями (рН, тест в’язкості (Viscosity), тип системи (Type system), мукоадгезивні властивості (Mucoadhesive)). Методи дослідження: реологічні дослідження (тест в’язкості досліджених гелів, амплітудний, частотний, мукоадгезивний тести, тест тиксотропії) виконано в осциляційному режимі на модульному компактному реометрі Anton Paar MCR 302 (CP50-1 SN71317), що порівняно з циліндричними пристроями потребує значно меншої кількості зразка гелю, а також дає змогу в осциляційному режимі проводити заплановані тести. Температуру в дослідах забезпечували вбудованим термостатом (Peltier temperature control for concentric cylinder systems, C-PTD 200).
Розроблення складу безпечного оромукозного гелю з антагоністом IL-1β для лікування запальних захворювань пародонта
Dmytriieva O. O. - ORCID ID: 0009-0003-5259-2212; Bielenichev I. F. - ORCID ID: 0000-0003-1273-5314; Burlaka B. S. - ORCID ID: 0000-0003-4539-7331.
Keywords: IL-1β; oromucosal gel; pharmaceutical development; pharmacological studies; acute toxicity test; оромукозний гель; фармацевтична розробка; фармакологічні дослідження; гостра токсичність